L'innovation de Produit Au Sein Des Pme Algeriennes : Analyse des Facteurs Cles de Succes Dans la Region Nord Ouest - Hafida, Haddad; Amari, Salah Eddine Sofiane; Chouam, Bouchama (جامعة حسيبة بن على الشلف - كلية العلوم الاقتصادية والعلوم التجارية وعلوم التسيير, 2018)
The importance of a product innovation is known, it has a considerable impact on the sales and profits of the company. In this sense, our research aims to identify the key success factors of the new products developed and launched by Algerian SME. The results we have achieved underline, on the one hand, the awareness of SME managers of the importance of product innovation for the existence and continuity of the company in the market. On the other hand, despite the difficulties encountered in the development of new products, particularly in relation to factors relating to the quality of the development process of new products, we find that practices exist in SMEs but that they are not formal.
Keywords: الجزائر -- إدارة الشركات -- إدارة الجودة الشاملة